Vigilância genômica da transmissão de dengue e zika no Brasil - Talita Émile Ribeiro Adelino (2022)
Mosquito-borne arboviruses are considered important challenges for public health in Brazil, especially in recent years, where the epidemiological scenario has been marked by the co-circulation of different arboviruses, including dengue (DENV), Zika (ZIKV), chikungunya (CHIKV) and yellow fever (YFV). Despite this, there is a paucity of updated data on these viruses genetic diversity and transmission dynamics in Brazil. Therefore, the aim of this work was to carry out genomic monitoring of DENV (DENV1 and DENV2 serotypes) and ZIKV during the recent epidemics of these viruses in Brazil. For this, were generated 250 complete or near-complete viral genomes (DENV1=57, DENV2=170 and ZIKV=23) and combined with epidemiological information for more contextual data about these viruses. The results of this study provided a comprehensive assessment of the recent dengue and Zika epidemics across Brazilian regions and highlighted the importance of ongoing surveillance efforts to better understand arbovirus epidemics in the country.